Dietary Kluyveromyces marxianus hydrolysate alters humoral immunity, jejunal morphology, cecal microbiota and metabolic pathways in broiler chickens raised under a high stocking density - Konkawat Rassmidatta; Yongyuth Theapparat; Nithikarn Chanaksorn; Paolo Carcano; Kazeem D. Adeyemi; Yuwares Ruangpanit (Poultry Science, 2024)
ABSTRACT: This study investigated the impact of dietary supplementation with hydrolyzed yeast (Kluyveromyces marxianus) on growth performance, humoral immunity, jejunal morphology, cecal microbiota and metabolic pathways in broilers raised at 45 kg/m2. A total of 1,176 mixed sex 1-day-old Ross 308 broilers were distributed into 42 pens and randomly assigned to either the control group, the control + 250 g hydrolyzed yeast (HY)/ton, 250HY group, or the control + 500 g HY/ton, 500HY group for 42 d. HY did not affect growth performance. However, HY reduced (P < 0.05) mortality at 25 to 35 d. Dietary HY lowered the heterophil/lymphocyte ratio and enhanced the villus height/crypt depth ratio and Newcastle disease titer (P < 0.05). Compared with HY250 and the control, HY500 upregulated (P < 0.05) IL-10. HY enhanced the α diversity, inferring the richness and evenness of the ceca microbiota. HY500 had greater β diversity than the control (P < 0.05). Six bacterial phyla, namely, Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, Verrucomicrobia, and Cyanobacteria, were found. The relative abundance of Firmicutes was greater in the HY500 treatment group than in the HY250 and control groups. HY decreased the abundance of Actinobacteria. HY supplementation altered (P < 0.05) the abundance of 8 higher-level taxa consisting of 2 classes (Bacilli and Clostridia), 1 order (Lactobacillales), 1 family (Streptococcaceae), and five genera (Streptococcus, Lachnospiraceae_uc, Akkermansiaceae, PACO01270_g, and LLKB_g). HY500 improved (P < 0.05) the abundance of Bacilli, Clostridia, Lactobacillales, Streptococcaceae, Streptococcus, PACO01270_g, and Lachnospiraceae_uc, while HY250 enhanced (P < 0.05) the abundance of Akkermansiaceae and LLKB_g. HY improved the abundance of Lactobacillus and Akkermansia spp. Minimal set of pathway analyses revealed that compared with the control, both HY250 and HY500 regulated 20 metabolic pathways. These findings suggest that dietary K. marxianus hydrolysate, especially HY500, improved humoral immunity and jejunal morphology and beneficially altered the composition and metabolic pathways of the cecal microbiota in broilers raised at 45 kg/m2.